General Sports Injured and Reasons in Fencing Sport - ahmed, shaeama (Journal of Physical Education, 2010)
Fencing is primarily considered one of the most competitive sport games where a high amount of friction is occurred. according to the nature of the game. in the three weapons played(foil. Epee and Saber). Fencers are likely to get hurt or injured through the competitions or camps. When injured. a player might be unable to compete or maintain his performance. besides; the possibility of having another injury is highly expected. In order to have all these kinds of injuries decreased one has to exactly recognize the nature. positions and reasons of such injuries and that what the procedural research is meant to study using the descriptive method (Survey Study) which deals with the nature of targets.147 fencers have been deliberately chosen with a list of survey that contains types. areas and reasons of injuries. After having that list distributed on the accredited samples. statistical processes have been considered in accordance with sex. Results were displayed in tables and were analyzed and discussed. a number of conclusions and recommendations have been inferred in terms of trying as far as possible to reduce or prevent physical injuries also to get the fencers set in competitions so they can give the best they have.